2017
DOI: 10.1371/journal.pone.0181719
|View full text |Cite
|
Sign up to set email alerts
|

Is intraindividual reaction time variability an independent cognitive predictor of mortality in old age? Findings from the Sydney Memory and Ageing Study

Abstract: Intraindividual variability of reaction time (IIV RT ), a proposed cognitive marker of neurobiological disturbance, increases in old age, and has been associated with dementia and mortality. The extent to which IIV RT is an independent predictor of mortality, however, is unclear. This study investigated the association of IIV RT and all-cause mortality while accounting for cognitive level, incident dementia and biomedical risk factors in 861 participants aged 70-90 from the Sydney Memory and Ageing Study. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…These results can be interpreted in view of the evidence suggesting that the neurodegenerative process of aging has an initial impact in the white matter, affecting cortical pathways in a fronto occipital gradient, leading to impairments in executive function and processing speed. 13,24,25 Our findings are in agreement with previous studies that point out reaction time assessments as sensitive early marker of subtles changes in cognition of community-dwelling health older adults and pathological aging, [6][7][8] indicator of quality of life, 26 as well a predictor of functional decline 27 and shorter time to death 28 and is associated with functional mobility. 29 The neuroprotection of alpha motor neurons and motor endplate found in senile exercised rats 30 may also support the shorter movement latency founded in exercised groups.…”
Section: Resultssupporting
confidence: 92%
“…These results can be interpreted in view of the evidence suggesting that the neurodegenerative process of aging has an initial impact in the white matter, affecting cortical pathways in a fronto occipital gradient, leading to impairments in executive function and processing speed. 13,24,25 Our findings are in agreement with previous studies that point out reaction time assessments as sensitive early marker of subtles changes in cognition of community-dwelling health older adults and pathological aging, [6][7][8] indicator of quality of life, 26 as well a predictor of functional decline 27 and shorter time to death 28 and is associated with functional mobility. 29 The neuroprotection of alpha motor neurons and motor endplate found in senile exercised rats 30 may also support the shorter movement latency founded in exercised groups.…”
Section: Resultssupporting
confidence: 92%
“…Cognitive abilities are associated with health literacy, as people with lower cognitive function may be less able to engage in a healthy lifestyle and are less able to follow specialist instructions [19,29]. Additionally, people with lower cognition are unable to engage in a healthy lifestyle [22,30]. Moreover, cognitive functions might affect health as a part of a multi-dimensional concept like frailty, where it works along with other factors such as exhaustion, weight loss, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that cognitive decline, on the contrary, decreases the risk of cancer mortality [20]. Moreover, previous studies found that specific cognitive functions such as short-memory or cognitive speed may be differently associated with mortality than the total cognitive score [21,22]. This study explored associations between different cognitive functions and different causes of death accounting for significant covariates in the representative sample.…”
Section: Introductionmentioning
confidence: 95%
“…IIV is a behavioral representation of the transient fluctuation of RT over a given number of trials related to various aspects of information processing. These include (but are not limited to) attentional control and lapses, stimulus-and post-perceptual-processes and strategies, the functional and structural integrity of white and grey matter, and the status of distributed neural, and neurobiological networks [26,27,[42][43][44][45][46][47][48][49][50][51][52][53][54]. Although RT and IIV can correlate (i.e., slower RT associated with greater IIV), thus appearing to share common networks, the relationship between them is not always linear.…”
Section: Intra-individual Variability Of Reaction Timementioning
confidence: 99%